ANALISIS INTEGRASI NILAI KEISLAMAN AKHLAKUL KARIMAH DAN IMTAQ DALAM BUKU PEMBELAJARAN BAHASA INDONESIA KELAS III DI MADRASAH IBTIDAIYAH - Febby Lusita, Putri; Kristi Mulyani, Petra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article examines the extent to which the school’s vision is integrated into the Indonesian language textbook Grade III used in Madrasah Ibtidaiyah. The key vision points highlighted are Akhlakul Karimah (noble character) and Imtaq (faith and piety). The book was analyzed using a coding process based on the principles of Ahlussunnah Wal Jama’ah as upheld by Nahdatul Ulama. Each section of the textbook was examined by identifying keywords related to the indicators of Akhlakul Karimah and Imtaq. The content analysis revealed that moral values such as honesty, discipline, tolerance, and cooperation are reflected in several specific topics within the textbook. Similarly, values of faith such as humility (tawadu’), respect (ta’dzim), and honor (taqriman) appear in some of the material. However, other crucial aspects such as patience and a deep appreciation of the Qur’an and Hadith are not explicitly portrayed. The presence of Nahdlatul Ulama's principles in the Indonesian language textbook calls for educators to strengthen and evenly distribute Islamic values during the teaching and learning process. Therefore, it is essential for curriculum developers to pay greater attention to the integration of Islamic values aligned with Ahlussunnah Wal Jama’ah, as a foundation for shaping students’ character.